Liability of Land Deed Official (The PPAT) on Falsifying Document Under Indonesian Land Regulations - Muhammad Ilham Sumartoputra; Firman Turmantara Endipradja (Magister Kenotariatan Universitas Pasundan, 2020)
Head of Sub-District as Temporary Land Registrar can be said to have the same authority as PPAT as official land deed maker, however in practice the Sub-District Head as Temporary PPAT often ignores existing regulations regarding deed, such as not reading the deed so that the contents of the land sale certificate cannot be understood by party. In addition, in the contents of the document there are many